ANALYSIS OF LABOR DISTRIBUTION BY OUTSOURCING COMPANIES AT PT GAMA PRIMA KARYA : (Study at PT. Fumakilla Indonesia) - Krisanty; Sari Marliani; July Juliawaty (PT. Berkah Digital Teknologi, 2025)
Purpose: This study aims to analyze the recruitment process, selection criteria, and employee performance at PT Fumakilla Indonesia. The main focus of the study is to identify problems related to the return of workers who do not meet the standards desired by the company. Research Methodology: The research was conducted at PT Fumakilla Indonesia located at JI. Sudirman No.5, RT.006/RW.016, Kayuringin Jaya, South Bekasi, Bekasi City, West Java. The research methodology includes: Recruitment Process Observation: Observing recruitment steps, including vacancy announcements and specified requirements. Employee Selection: Examining the types of tests applied, such as written tests and speed tests. Labor Distribution: Examining how workers recruited through outsourcing are forwarded to the company and the form of employment contracts provided. Employee Performance: Analyzing employee performance after work, including absenteeism rates and compliance with superiors' directives. Results: The results of the study indicate that: 1). Recruitment Process: The company sets minimum criteria of high school education, maximum age of 24 years, and is open to both experienced and unexperienced. 2). Selection: Selection is carried out through a written test followed by a speed test, which aims to assess the ability of prospective employees. 3). Distribution of Workforce: Workforce accepted through outsourcing is distributed to the company with a clear form of employment contract. 4). Employee Performance: Employees accepted show a good level of absenteeism and follow directions from superiors, although there are challenges in retaining workers who meet the criteria. Limitations: This study has several limitations, including: The study was only conducted at PT Fumakilla Indonesia, so the results may not be generalizable to the industry as a whole. The data collected is limited to a certain period and may not cover all variables that affect employee performance. Contribution: This study makes an important contribution to the understanding of the effectiveness of outsourcing in workforce distribution. In addition, this study highlights the importance of alignment between employee qualifications and company expectations, and provides recommendations for improving recruitment and selection processes to be more effective in meeting the need for a quality workforce.